2015
DOI: 10.1152/ajplung.00362.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Kv7 channels in responses of the pulmonary circulation to hypoxia

Abstract: Hypoxic pulmonary vasoconstriction (HPV) is a beneficial mechanism that diverts blood from hypoxic alveoli to better ventilated areas of the lung, but breathing hypoxic air causes the pulmonary circulation to become hypertensive. Responses to airway hypoxia are associated with depolarization of smooth muscle cells in the pulmonary arteries and reduced activity of K+ channels. As Kv7 channels have been proposed to play a key role in regulating the smooth muscle membrane potential, we investigated their involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…Detrimental effects of vascular K v 7 loss have been reported in experimental models of essential hypertension (Barrese et al, 2018;Carr et al, 2016;Jepps et al, 2011) and diabetes (Morales-Cano et al, 2015. Likewise, several studies suggest that K v 7 channels may also be impaired in murine models of PH (Morales-Cano et al, 2014;Morecroft, Murray, Nilsen, Gurney, & MacLean, 2009;Sedivy et al, 2015). It is therefore likely that the impairment of K v 7 channels in the pulmonary circulation could have detrimental consequences associated with an altered response to the NO/cGMP pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detrimental effects of vascular K v 7 loss have been reported in experimental models of essential hypertension (Barrese et al, 2018;Carr et al, 2016;Jepps et al, 2011) and diabetes (Morales-Cano et al, 2015. Likewise, several studies suggest that K v 7 channels may also be impaired in murine models of PH (Morales-Cano et al, 2014;Morecroft, Murray, Nilsen, Gurney, & MacLean, 2009;Sedivy et al, 2015). It is therefore likely that the impairment of K v 7 channels in the pulmonary circulation could have detrimental consequences associated with an altered response to the NO/cGMP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of BKCa channels has been shown to contribute to NO‐induced relaxation (Bolotina et al, ; Robertson et al, ), we found that the selective inhibitor iberiotoxin did not affect the enhanced K v current or the relaxation induced by DEA‐NO. K v 7 channels have recently emerged as key players regulating systemic (Chadha, Zunke, Zhu, et al, ; Khanamiri et al, ; Mani et al, ; Morales‐Cano et al, , ) and pulmonary (Joshi, Sedivy, Hodyc, Herget, & Gurney, ; Ng et al, ; Sedivy et al, ) vascular tone. Accordingly, we observed that the K v 7 inhibitor XE991 consistently depolarized the membrane potential but to a lower extent (3 mV) than previously reported (6 mV, Eid & Gurney, , and 15 mV, Joshi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic and pulmonary hypertensive conditions have been reported to be associated with a reduction in KCNQ4 mRNA and Kv7.4 protein in arterial myocytes, while KCNQ5 mRNA levels were unaltered (Chadha et al, 2012;Khanamiri et al, 2013;Sedivy et al, 2015). The selective loss of Kv7.4 subunits would likely shift the stoichiometry of the functional Kv7 channels toward a predominantly Kv7.5 channel phenotype.…”
Section: Pka-dependent Regulation Of Vascular Kv7 Channelsmentioning
confidence: 99%
“…While symptomatic hypotension has been reported as an adverse event after oral administration of high doses of retigabine in phase I clinical trials [17], retigabine has demonstrated the beneficial effect of reducing acute hypertension induced by co-administration of angiotensin II plus arginine vasopressin in rats [18]. Furthermore, the Kv7 channel activator flupirtine has been reported to reduce pulmonary hypertension in rodent models [19, 20]. Whether Kv7 channel blockade could be useful to improve hemodynamics and stabilize blood pressures in hypotensive disease processes, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%